Daclatasvir plasma level and resistance selection in HIV patients with hepatitis C virus cirrhosis treated with daclatasvir, sofosbuvir, and ribavirin. (August 2016) - Parisi, Saverio G.; Loregian, Arianna; Andreis, Samantha; Nannetti, Giulio; Cavinato, Silvia; Basso, Monica; Scaggiante, Renzo; Dal Bello, Federico; Messa, Lorenzo; Cattelan, Anna Maria; Palù, Giorgio
Highlights: Low daclatasvir levels allowed the selection of resistance-associated variants. Quantitation of daclatasvir levels in HIV–hepatitis C virus (HCV) cirrhotic patients on highly active antiretroviral therapy is suggested. Resistance testing is suggested even at low HCV RNA levels. Summary: Objectives: Effective treatment with direct-acting antiviral drugs against hepatitis C virus (HCV) is a medical need in cirrhotic HIV–HCV co-infected patients. Methods: This study investigated the plasma levels of daclatasvir (DCV) and ribavirin (RBV) in HIV–HCV co-infected subjects treated with DCV, sofosbuvir, and RBV. Drug concentrations were quantified using validated high-performance liquid chromatography methods with ultraviolet detection. The HCV non-structural protein 5A and non-structural protein 5B coding regions were analyzed by population-based sequencing. Results: DCV was dosed at week 4 and at week 8 of treatment, and RBV at week 8. One patient had the lowest DCV level, corresponding to 32.7% of the overall median value of the other patients at week 4 and about 40% at week 8. The Y93H variant was detected in this subject at weeks 8, 16, and 20 of treatment, but not before treatment or at day 2, and the patient experienced virological failure. Another subject with the Y93H variant at baseline and appropriate DCV levels had HCV RNA <12 IU/ml at week 12 and undetectable at week 16. Conclusions: Sub-optimal DCV drug levels allow the selection of resistance-associated variants and fail to contribute to antiviral activity. No definite reason for the low DCV level was found. Quantifying the drug is suggested in difficult-to-treat patients.